Early Endothelial Activation in a Mouse Model of Graft vs Host Disease Following Chemotherapy - Pereira, Melrine; Lee, Natasha Ting; Noonan, Jonathan; Willcox, Abbey E. H.; Calvello, Ilaria; Georgy, Smitha Rose; Selan, Carly; Chia, Joanne S.; Hauw, Wayne; Wang, Xiaowei; Peter, Karlheinz; Robson, Simon C.; et al. (Frontiers in Immunology, 2021)
Allogenic hematopoietic stem cell transplant (allo-HSCT) can lead to sinusoidal obstruction syndrome (SOS) and graft-versus-host disease (GvHD) in some individuals. GvHD is characterised by an immune triggered response that arises due to donor T cells recognizing the recipient tissue as “foreign”. SOS results in impaired liver function due to microvascular thrombosis and consequent obstruction of liver sinusoids. Endothelial damage occurs following chemotherapy and allo-HSCT and is strongly associated with GvHD onset as well as hepatic SOS. Animal models of GvHD are rarely clinically relevant, and endothelial dysfunction remains uncharacterised. Here we established and characterised a clinically relevant model of GvHD wherein Balb/C mice were subjected to myeloablative chemotherapy followed by transplantation of bone marrow (BM) cells± splenic T-cells from C57Bl6 mice, resulting in a mismatch of major histocompatibility complexes (MHC). Onset of disease indicated by weight loss and apoptosis in the liver and intestine was discovered at day 6 post-transplant in mice receiving BM+T-cells, with established GvHD detectable by histology of the liver within 3 weeks. Together with significant increases in pro-inflammatory cytokine gene expression in the liver and intestine, histopathological signs of GvHD and a significant increase in CD4+ and CD8+ effector and memory T-cells were seen. Endothelial activation including upregulation of vascular cell adhesion molecule (VCAM)- 1 and downregulation of endothelial nitric oxide synthase (eNOS) as well as thrombosis in the liver indicated concomitant hepatic SOS. Our findings confirm that endothelial activation is an early sign of acute GvHD and SOS in a clinically relevant mouse model of GvHD based on myeloablative chemotherapy. Preventing endothelial activation may be a viable therapeutic strategy to prevent GvHD.